Analisis Tingkat Popularitas Produk Penjualan Kue Menggunakan Metode Analytical Hierarchy Process - Spastika, Galuh Mreta; Safitri, Elfira; Basriati, Sri; Soleh, Mohammad (Universitas Negeri Gorontalo, 2025)
This research explains the decision-making system in determining problems using the Dapoer Zahra case study in Pekanbaru. This research aims to measure the popularity of cake products at Dapoer Zahra Pekanbaru using the Analytical Hierarchy Process (AHP) method, as well as providing product recommendations that are worthy of prioritization based on the analysis results. AHP works by comparing each criterion in pairs to find out which one is more important. After the weight of each criterion is determined, cake products are assessed based on these criteria. The final result is a product ranking from most to least popular, which can be used as a basis for decision making in business management. Based on the research results, it was found that taste is the most important criterion in the level of popularity of cake sales products at Dapoer Zahra at 42.98%, price at 40.99% and finally the appearance criterion at 16.04%. The Marble Cake alternative has the highest level of product popularity with 28.50%, Chiffon Cake with 19.56%, Baked Brownies with 17.34%, Tape Cake with 13.93%, Roll Cake with 10.38%, and the last one is Bolu Banana with 10.29%. The results of the analysis show that Marmer Cake has the highest priority level compared to other types of cakes based on the criteria of price, taste, and appearance. This shows that Marmer Cake is considered superior in terms of taste that consumers like, competitive prices, and attractive product appearance. These advantages can be used as a reference by Dapoer Zahra to strengthen business strategies, such as increasing Marmer Cake production capacity, expanding flavor variations, or conducting special promotions for this product.